Determination of Pure Health Insurance Premiums Using Generalized Linear Models (GLM) with Poisson Distribution - Oktaviani, Devani; Zahra, Nabila; Halim, Nurfadhlina Abdul (International Journal of Global Operations Research, 2024)
Insurance companies need a method to help companies determine premium prices that are appropriate to the risks they face. In other words, it is also necessary to know the variables that influence premium prices using Generalized Linear Models (GLM) by generalizing the linear regression model to model the relationship between the dependent variable and the independent variable. The aim of this research is to determine the variables that influence premium prices and determine the pure health insurance premium using the GLM method.